Persian mythology - Hinnells, John R. (London New York Hamlyn, 1973)
Discusses the mythology of ancient Persia and of religions which have flourished there, notably Zoroastrianism.
Includes index.
Bibliography: p. 138-139.
Keywords: Mythology, Iranian; Zoroastrianism; Mythology, Iranian; Zoroastrianism